A questão identitária na personagem Ifemelu em Americanah: um estudo sobre o cidadão em trânsito cultural - Morato, Ana Maria Cassiano (2020)
The aim of this study, based on the book Americanah, which was written by the Nigerian and activist author, Chimamanda Ngozi Adichie, is to analyze the identity of an individual who heads from one country to another on account of many reasons. Taking this into consideration, the general objective is to demonstrate that once one had his/her own identity changed, how it would be possible to keep some characteristics of the original one. To do so, the strategies that Ifemelu (Americanah’s protagonist) used will be shown throughout the analysis. The specific objectives are: (a) to investigate what strategies the protagonist used to deconstruct and reconstruct her own identity with trates of the original one; (b) analyze that she discovered herself as a black woman in the USA; (c) demonstrate that after living such a long period in two different places, Ifemelu had her identity transformed and shared, and also discovered how it was to feel displaced not only in America, but also in her own country; (d) also investigate that the feeling of belonging to both countries or neither of them, it is common to people who live in two or more countries and, lastly, (e) it will be analyzed that due to the fact of not knowing where she belonged to also made her having issues to recognize her true home. In order to do such analysis, the theoretical contributions count on names of authors who, not only are researchers of these subjects, but also have been through this experience of displacement and had their own identity shared as well as Adichie, among them are: Stuart Hall (1998; 2003), Homi Bhabha (1990;1998) and Edward Said (1999). Besides these ones, to analyze the concept of identity and race the research counted on Chris Barker (2004) and Raymond Williams (1983); considering globalization the chosen authors were Anthony Giddens (1990) and Jane Jackson (2014); hibridization Tomaz Tadeu Silva (2006) and Nestor Garcia Canclini (2003;2007) were the chosen researchers; to displacement the research counted on Said (1999); and to analyze the concept of home, belonging and homesickness, Bauman (1996) was the chosen author, among others.